HUBUNGAN PENGETAHUAN PASIEN TBC TENTANG PENYAKIT TBC DENGAN KEPATUHAN MINUM OBAT ANTI TUBERKULOSIS (OAT) - Agustina, Emi; Cahyono, Safran (Akademi Keperawatan Pamenang, 2012)
Tuberkulosis is an infectious disease caused by Mycobacterium. These germs enter the body through the respiratory system, digestive tract and open sores on the skin (Price, 2006: 852). Tuberkulosis treatment Tuberkulosis patient is taking medicine for Anti Tuberkulosis (OAT), which overall treatment can reach 6-12 months. In this case requires knowledge about TB disease and compliance in taking drugs to treat Tuberkulosis (TB), for good compliance will also form a good behavior. The purpose of this study is to determine the relationship of knowledge about TB disease TB patients with anti-Tuberkulosis medication adherence (OAT). Design used in this study is cross sectional analytic, samples taken from TB patients who seek treatment at health centers Plemahan Puhjarak Kediri District with a large sample of 20 respondents with a total sampling techniques. Processing data using descriptive analysis test with cross tabulation and statistical test. Results from contingency coefficient statistical test obtained results (p) = 0,000 and Î± = 0,05 so that p < Î± hence H0 refused and H1 accepted as such can be said that there was a correlation between the TB patient knowledge about TB disease with adherence to drink Anti Tuberkulosis Drugs ( OAT).From the description above, it can be concluded that most respondents have good knowledge about TB disease, dutifully carrying out anti-Tuberkulosis medication (OAT) and there is a relationship between TB patient knowledge about TB disease with anti-Tuberkulosis medication kapatuhan (OAT) so that more and better knowledge of TB patients about the more obedient TB disease in TB patients taking the medicine. Â Keywords: knowledge, compliance, TB.